Enzymatic Hydrolysis of Mannan from Konjac (Amorphophallus sp.) Using Mannanase from Streptomyces lipmanii to Produce Manno-oligosaccharides - Sasongko, Ashadi; Yopi,; Rahmani, Nanik; Lisdiyanti, Puspita; Saepudin, Endang (UI Scholars Hub, 2015)
Mannan is an abundant polysaccharide that can be found in konjac (Amorphophallus sp.). Mannan can be enzymatically hydrolyzed using mannanase to produce manno-oligosaccharides which can be used as a prebiotic. The aims of this research are to determine the production time of mannanase from Streptomyces lipmanii, perform enzyme characterization, optimize the hydrolysis time, and characterize the hydrolysis product. A qualitative assay using the indicator Congo red showed that S. lipmanii generated a clear zone, indicating that S. lipmanii produced mannanase in konjac medium and possessed mannanolytic activity. Enzyme activity was determined through reducing sugar measurement using the dinitrosalycylic acid method, and optimum enzyme production was achieved at the second day of culture. Characterization of the enzyme showed that hydrolysis was optimum at pH 7 and at a temperature of 50 oC. The reducing sugar content was increased by an increasing the hydrolysis time, and reached an optimum time at 2 h. The degree of polymerization value of three was achieved after 2 h hydrolysis of mannan from konjac, indicating the formation of oligosaccharides. Analysis by thin layer chromatography using butanol, acetic acid, and water in a ratio of 2:1:1 as eluent showed the presence of compounds with a retention time between those of mannose and mannotetrose. Confirmation was also performed by HPLC, based on the retention time.